The Management and Evaluation of Independent Project Portfolios under Uncertainty and Projects Incompatibility - Hadi Mokhtari; Zeinab Habibi (مدیریت مهندسی و رایانش نرم)
This research focuses on evaluating and proposing some approaches in order to choose the most economic projects under risk and uncertainty. In this investigation, the considered projects are independent and naturally selecting multiple options, as a project portfolio, is possible. The restrictive criterion for the investor in selecting large-scale portfolios is the limited available budget and capital that determine which projects are economic and can be selected. However, variations and inconsistencies in the economic utility of projects, which is caused by external uncertainties, is an important factor that should be considered in such evaluations. In this research, two different approaches are proposed for the economic evaluation of project portfolio under risk and uncertainty. The first approach is designed based on a normal distribution curve and the minimum coefficient of variation (CV), while the second one acts based on a corrected available budget and the maximum expected value. Finally, the results of the proposed approaches are evaluated and analyzed considering the presented sample problems.